Three essays on effective demand, economic growth and inflation - Kim, Jung Hoon (University of Ottawa (Canada), 2007)
The dissertation discusses the possibility of a reconciliation between neo-Kaleckian and classical (neo-Marxian/Sraffian) two-sector growth models, and it explores the issues relative to the long-run convergence of actual degrees of capacity utilization towards their normal values. In a simplified analytical framework, that examines regimes incorporating neo-Kaleckian and neo-Marxian/Sraffian perspectives, the thesis shows that the paradox of thrift and the paradox of costs hold both in the short run and in the long run. A more sophisticated two-sector Kaleckian model is also developed within a stock-flow consistent framework that includes conflicting-claim inflation and Kaldorian technical progress. Simulation results show that inflation-targeting policies based on the so-called 'Taylor rule' could remove the long-run paradoxes, leading to economic depression. These policies also fail to achieve normal rates of capacity utilization, because of 'path-dependency', in contrast to the arguments put forth by some neo-Marxists and the proponents of the neoclassical New Consensus. Furthermore, our empirical tests show that the Phillips curve has a horizontal segment within a large intermediate range of capacity utilization rates, using Canadian data over the last two decades. This horizontal Phillips curve implies that the adjustment mechanisms suggested by classical models just may not exist in reality during this time period. Therefore, the thesis offers some justification for using simple neo-Kaleckian growth models where effective demand plays a crucial role in the determination of capacity utilization, employment and growth, both in the short run and in the long run, and it suggests the use of expansionary fiscal policy and monetary policy as long as the economy remains within the intermediate range of capacity utilization. Key words: Two-Sector Growth Model; Long-Run Convergence; Paradox of Thrift; Paradox of Costs; Inflation; Phillips Curve; Monetary Policy; Stock-Flow Consistent Approach.
Keywords: Economics, General.; Economics, Theory.